(untitled) (Homoeopathy for All, 2023)
Polycystic Ovarian Disease PCOD) and infertility is a complex relationship and therefore shouldbe taken seriously at the onset itself. The correlation between PCOD and infertility peaks during the reproductive age of women, i.e.24 to 3 5 years.Polycystic Ovarian Disease (PCOD) is a medical condition which is characterized by hyperandrogenism and chronic anovulation. In female ovaries,estrogen & progesterone are the two hormones responsible for reproduction and hormonal imbalance in these levels can create PCOD. Many others hormones also contribute in causing PCOD like luteinizing hormones (LH), follicle stimulating hormone (FSH). The most prevalent problem that occurs in PCOD is the imbalance in the woman’s hormones that affects follicular growth during the ovarian cycle causing the affected follicle to remain in the ovary. The retained follicle forms into a cyst and with each ovarian cycle a new cyst is formed leading to multiple ovarian cyst.